DESENVOLVIMENTO DE UM EMPREENDIMENTO CERVEJEIRO E SEUS DESAFIOS ESTRATÉGICOS (ADMPG Journal, 2024)
This article aims to evaluate the planning, execution and direction of the strategies of a microbrewery (brewpub), during the pandemic period, located in the interior of Paraná. A case study was carried out, operationalized through interviews with the three founding partners and participant observation with the collection of information in the place where the facts and phenomena happened. We identified from the analysis of the case particularities that involved the opening of the business in a scenario of inhibition and financial crisis experienced in the country, mainly with regard to food services with face-to-face service. In this pandemic scenario, it was evident that good management of resources and efficient marketing made it possible to open the venture with significant success. We notice that planning contributed to making decisions about strategy more quickly. It is concluded, therefore, that the strategy adopted by the entrepreneurs overcame the difficulties imposed by the pandemic and achieved, above all, its goals and objectives. However, it was also possible to observe the role of the management process, which at the same time was able to overcome the initial challenges of the pandemic, but that is now having difficulties in operating in a less volatile market.